Places of contested power : conflict and rebellion in England and France, 830-1150 - Lavelle, Ryan (The Boydell Press, 2020)
The direct contestation of power played a crucial role in early medieval politics. Such actions, often expressed through violence, reveal much about established authorities, power and lordship. In this volume the hitherto neglected role of place and landscape in acts of opposition and rebellion is explored for its meaning and significance to the protagonists. It includes a consideration of a range of factors relevant to the choice of location for such events, and examines the declarations and motivations of political actors, from disaffected princes to independently minded nobles, as well as those who responded to rebellion, to show how places and landscapes became used in political disputes. These include both "public" and "private", religious, urban and rural space. Covering a long period in England and northern France, from the late Carolingian period through to the emergence of cross-Channel polities in the aftermath of the Norman Conquest, this book casts valuable light on the political relations of the early and central Middle Ages. RYAN LAVELLE is Professor of Early Medieval History in the Department of History at the University of Winchester